Islamic Education’s Responses to Social Changes and Community Behaviors - Sukino Sukino; Fauzan Fauzan (Faculty of Educational Sciences, Syarif Hidayatullah State Islamic University, 2020)
AbstractThis study explains three things that are significant in the context of change. First, how is the change in community behavior as a result of the development of the oil palm plantation industry in the village of Dak Jaya, secondly why the people of the Dak Jaya village have changed their behavior in publishing Islamic education, third, what are the dimensions of the Islamic education development so that people have increased interest in Islamic education. The research approach is qualitative, data collection methods with interviews and direct observation, data validity techniques using triangulation of sources and extension of observation. Data were analysed from the beginning of data collection through an interactive process that is the collection, reduction, display, and verification or conclusion drawing. The results of the study explained that (1) changes in people’s attitudes as a result of economic changes opening up information openness present new values in people’s lives so that people change behavior into hedonists, pragmatics and individualists, (2) the impact of life towards hedonists, pragmatics and individualists in society make anxious about the future of the young generation so that it grows positive responses that make religious education as the construction of religious values and religious humanism, (3) madrassas and Islamic boarding schools are considered as the foremost oasis of the future because they can provide excellent service, develop creativity and provide ecological literacy for a healthy life.AbstrakPenelitian ini menjelaskan tiga hal yang signfikan dalam konteks perubahan. Pertama bagaimana perubahan perilaku masyarakat sebagai akibat dari perkembangan Industri perkebunan kelapa sawit di desa Dak Jaya, kedua mengapa masyarakat desa Dak Jaya berubah perilakunya dalammerepos pendidikan Agama Islam, ketiga, dimensi apa dari lembanga pendidikan Islam sehingga masyarakat meningkat minatnya terhadap pendidikan Islam. Pendekatan penelitian adalah kualitatif, metode pengumpulan data dengan wawancara dan observasi langsung, teknik keabsahan data menggunakan triangulasi sumber dan perpanjangan pengamatan. Data dianalisis sejak awal pengumpulan data melalui proses interaktif yakni pengumpulan, reduksi, display dan verifkasi atau penarikan kesimpulan. Hasil penelitian menjelaskan bahwa (1) perubahan sikap masyarakat akibat dari perubahan perekonomian membuka keterbukaan informas menghadirkan nilai-nila baru dalam kehidupan masyarakat sehingga mengubah perilaku masyarkat menjadi hedonis, pragmatis dan individualis, (2) dampak dari kehidupan kearah hedonis, pragmatis dan individualis pada masyarakat membuat rasa cemas terhadap masa depan generasi muda sehingga tumbuh respon positif yakni menjadikan pendidikan agama sebagai konstruksi nilai religiusitas dan humnisme religious, (3) madrasah dan pondok pesantren dinlai sebagai oasis menemuka masa depan karena mampu memberikan layanan prima, mengembangkan kreativitas dan memberikan literasi ekologis untuk hidup sehat. How to Cite: Sukiono., Fauzan. (2020). Islamic Education’s Responses to Social Changes and Community Behaviors. TARBIYA: Journal of Education in Muslim Society, 7 (1), 29-47. doi:10.15408/tjems.v7i1.16717.